(untitled) (Revista Apotheke, 2018)
Carolina Paz São Paulo, Brazil, 1976 I am an artist and social scientist. Since 2008, I have been presenting my artworks in individual and collective exhibitions, special projects and art residency programs in Brazil, United States and Europe. I am co-founder and director of “Coletivo 2e1”, an artist run space and online network originaly based in São Paulo, Brazil. In 2013, I was the winner of Funarte Award in Recife, Brazil. I have working in education since 2000 as a professor and distance education specialist. My work vision is based on participatory practices. http://carolinapaz.com/cv